The Actual Meaning of Colombia Being Under the Social Rule of Law - Cabrera Suárez, Lizandro Alfonso (DIXI, 2018)
Aim: The exercise will consist in establishing the meanings of the concepts related to the principle of the Social Rule of Law. Methods: Indeed, what does it mean that Colombia is under the Social Rule of Law? The expression means that the constituents representing the people decided on a specific form of State and excluded others. But what characterizes it? Results: While being a supremely rich topic full of implications about which entire books could be written, it will be presented in a summarized manner trying to gather all the important elements of the discussion around it. Conclusions: If there is no Rule of Law, there is no democracy. The Social Rule of Law also strives for the realization of fundamental social rights.